2022
DOI: 10.1007/s10096-022-04483-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of selective decontamination on the intestinal microbiota as measured with IS-pro: a taxonomic classification tool applicable for direct evaluation of intestinal microbiota in clinical routine

Abstract: Selective decontamination of the digestive tract (SDD) is aimed at elimination of potential pathogenic microorganisms. In this study, the effect of SDD on gut microbiota was evaluated in a large homogenous group of elective colorectal cancer surgery patients. Rectal swabs were taken from 118 patients undergoing colorectal surgery. These patients were randomly assigned to receive perioperative SDD or to the control group (no SDD). Rectal swabs were taken prior to surgery, 3 days after commencing administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…47 48 It would be remiss to assume that because SDD was designed to control the abundance of GNAR, that they are the only affected taxa. 49 Previous studies of SDD in adults have reported reduced VAP and are variably associated with the reduction in HCAIs. 9 14 50 Of the Gammaproteobacteria, the Enterobacteriaceae represented the largest proportion of gut-resident GNAR in our study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…47 48 It would be remiss to assume that because SDD was designed to control the abundance of GNAR, that they are the only affected taxa. 49 Previous studies of SDD in adults have reported reduced VAP and are variably associated with the reduction in HCAIs. 9 14 50 Of the Gammaproteobacteria, the Enterobacteriaceae represented the largest proportion of gut-resident GNAR in our study.…”
Section: Discussionmentioning
confidence: 93%
“… 47 48 It would be remiss to assume that because SDD was designed to control the abundance of GNAR, that they are the only affected taxa. 49 …”
Section: Discussionmentioning
confidence: 99%